2017
DOI: 10.1002/ppul.23663
|View full text |Cite
|
Sign up to set email alerts
|

The modified respiratory index score (RIS) guides resource allocation in acute bronchiolitis

Abstract: This simple respiratory tool predicts for the need for respiratory support, intravenous hydration, and a significant hospital stay of 2 days or more. Pediatr Pulmonol. 2017; 52:954-961. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…In contrast, there was no statistical difference in the modified RIS score in patients who were hospitalized compared to those discharged. This could be due to the small subset study population and the milder severity with a lower modified RIS as compared to the main cohort . This observation highlights the potential superiority and utility of nasal HMGB1 as a potential predictor for resource utilization for bronchiolitis as compared to modified RIS alone.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast, there was no statistical difference in the modified RIS score in patients who were hospitalized compared to those discharged. This could be due to the small subset study population and the milder severity with a lower modified RIS as compared to the main cohort . This observation highlights the potential superiority and utility of nasal HMGB1 as a potential predictor for resource utilization for bronchiolitis as compared to modified RIS alone.…”
Section: Discussionmentioning
confidence: 92%
“…This was part of a larger study that focused on a clinical prediction score for bronchiolitis . We recruited a convenience sample of patients that attended the ED during office hours (8am‐6pm) on weekdays.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another scoring system, the modified Respiratory Index Score (RIS), was found to be a reasonable predictor of the need for hospital admission in a singlecenter study in Singapore. 54 A large multicenter clinical trial did not show any benefit of nebulized hypertonic saline for reduction of hospital admissions in acute bronchiolitics in an emergency department setting. 55 In a review, Hancock et al 56 A randomized, double blind placebo controlled multicenter trial carried out in Spain found that dexamethasone (0.25 mg/kg/dose every 6 h, for 48 h) shortened the duration of illness due to parapneumonic effusion, when coupled with antibiotics.…”
Section: Respiratory Syncytial Virus (Rsv) Infection In Infants and Ymentioning
confidence: 94%
“…Balaguer et al found the clinical severity score known as Bronchiolitis Score of Sant Joan de Déu (BROSJOD) to be a reliable indicator of disease severity for acute bronchiolitis between independent observers. Another scoring system, the modified Respiratory Index Score (RIS), was found to be a reasonable predictor of the need for hospital admission in a single‐center study in Singapore . A large multicenter clinical trial did not show any benefit of nebulized hypertonic saline for reduction of hospital admissions in acute bronchiolitics in an emergency department setting .…”
Section: Introductionmentioning
confidence: 96%